Hydration kinetics of cereal and pulses: New data and hypothesis evaluation - Miano A.C. (2018)
Consejo Nacional de Ciencia, Tecnología e Inovación Tecnológica (CONCYTEC, Peru) . Grant Number: 272-2015-FONDECY